Perjamuan Pneumatik: Titik Temu Pandangan Calvin Dengan Teologi Pantekosta - grace, Lily; Grace, Lyly (JURNAL LUXNOS, 2025)
Academic literature within Pentecostal circles reveals a lack of adequate theological reflection on the Lord’s Supper. Pentecostal theologians themselves acknowledge the limited development and theological contribution in this area. This study seeks to offer a constructive theological contribution by engaging in a conceptual dialogue between John Calvin’s view and Pentecostal theology regarding the Lord’s Supper. Employing a qualitative descriptive method with a literature analysis approach, the study finds that the Pentecostal understanding tends to align with Zwingli’s symbolic view, which appears inconsistent with the Pneumatological nature of Pentecostal theology. In contrast, Calvin emphasizes the spiritual presence of Christ through the work of the Holy Spirit. This research identifies a common ground between Calvin’s theology and Pentecostal thought in the central role of the Holy Spirit in the Lord’s Supper. Consequently, the Lord’s Supper may be reinterpreted as a Pneumatic Supper, resonating with the Pentecostal experience of encountering Christ through the Spirit.